2017
DOI: 10.1186/s12957-017-1141-4
|View full text |Cite
|
Sign up to set email alerts
|

The stratification of patient risk depending on the size and ratio of metastatic lymph nodes in papillary thyroid carcinoma

Abstract: BackgroundThe aims of this study were to identify the clinical significances of the size of metastatic lymph node (mLN) and LN ratio (LNR) and to attempt to create a risk stratification for papillary thyroid carcinoma (PTC) patients.MethodsWe investigated the 435 PTC patients who underwent radioactive iodine (RAI) ablation treatment following thyroid surgery. The patients were classified into two groups (micrometastasis (pN1mic) ≤ 0.2 cm and macrometastasis (pN1mac) > 0.2 cm) and were stratified into the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
(35 reference statements)
1
22
0
Order By: Relevance
“…There were great differences in cervical LNM of PTC patients in our hospital and there was no uni ed standard for the number of LNs dissections per patient. A quite few [12][13][14] articles found that a greater NMLNs might be associated with lower survival. Similarly, patients with NMLNs ≥5 were divided into intermediate risk in the improved risk strati cation of recent ATA guideline [1].…”
Section: Patients Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…There were great differences in cervical LNM of PTC patients in our hospital and there was no uni ed standard for the number of LNs dissections per patient. A quite few [12][13][14] articles found that a greater NMLNs might be associated with lower survival. Similarly, patients with NMLNs ≥5 were divided into intermediate risk in the improved risk strati cation of recent ATA guideline [1].…”
Section: Patients Selectionmentioning
confidence: 99%
“…On the one hand, many scholars have tried to establish a standard for recurrence risk strati cation of PTC patients according to the characteristics of metastasis LNs. They found that the risk of recurrence was higher among PTC patients with larger metastatic LNs or higher mLNR [11][12][13][14]. As declared in the most recent American Thyroid Association (ATA) risk strati cation system, the recurrence rate of pN1 PTC with ≤5 LNs involved or >5 LNs involved is 5% and 20%, respectively [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, an enlarged lymph node with only a small metastatic focus may represent an efficient local immune response compared to a smaller node that has been completely replaced by metastatic tumor. Additionally, none of our 245 pN+ patients had a metastatic lymph node or a metastatic focus that measured greater than 6 cm, meaning that no OSCC patient was eligible for the pN3a category based on maximal lymph node size as per AJCC8.Studies in thyroid cancer have analyzed the role of the size of the metastatic focus within the involved node instead of the overall size of the metastatic lymph node, showing that it has value in outcomes prediction [18][19][20][21][22]. But to the best of our knowledge, Deng et al20 are the only authors that have evaluated the actual relationship between the size of the largest metastatic lymph node and the size of the largest metastatic focus.…”
mentioning
confidence: 99%